Keanekaragaman Dan Indeks Nilai Penting Tumbuhan Mangrove Di Kecamatan Gresik, Kebomas Dan Manyar Kabupaten Gresik - Styaningsih, Krisna; Karunia Binawati, Diah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2023)
Abstract Mangroves are a group of plants that live in coastal areas, which are a group of plants consisting of various species, but have similarities in terms of morphological and physiological adaptation to habitats that are influenced by tides (transitional ecosystems between land and waters around river mouths). Gresik is a district that has a mangrove ecosystem and not much research has been done. This study aims to determine the index of diversity value, important value index and environmental factors of mangroves in Gresik, Kebomas and Manyar Districts, Gresik Regency. Data collection at each observation station was 6 plots with a plot size of 10x10 m. The results showed that the Shannon Wiener (H') diversity value index was station 1 (0.62146), station 2 (1.64737) and station 3 (2.22906). The highest significance index for the category of poles and trees was at station 1 (85.11101), station 2 (24.39005) and station 3 (17.22808). The index of significance value for the categories of seedlings and saplings was highest at station 1 (80,80808), station 2 (52,96099) and station 3 (37,68549). Based on the results of the ANOVA test, the thickness of the mud at stations 1, 2 and 3 did not differ significantly so that it had no effect on mangrove diversity. The results of the salinity ANOVA test at stations 1, 2 and 3 differ significantly so that it can affect the diversity of mangroves. The results of the ANOVA test of soil pH at stations 1, 2 and 3 were significantly different so that it could affect the diversity of mangroves. Keywords: Mangrove, diversity index, important value index, environmental factors, Gresik Regency.